Kepatuhan Ibu Hamil Melakukan Kunjungan Antenatal Care (ANC) pada Masa Pandemi Covid-19 - Komang Intan Dewanggayastuti; I Dewa Ayu Ketut Surinati; Ni Nyoman Hartati (Jurnal Gema Keperawatan, 2022)
Maternal and newborn mortality rates are still a concern for the government, including during the Covid-19 pandemic. Monitoring physical and mental health including fetal growth and development is one of the efforts to prevent maternal death. The research objective was to describe the compliance of pregnant women in conducting antenatal care (ANC) visits during the Covid-19 pandemic at Public Healt Center. The methode of this research was discriptif design. The samples were consisted of 63 respondents selected with Purposive sampling technique. The results of this study were visits to ANC first to sixth visits, only visits 1 and 4 were carried out 100%, other visits had not reached 100% and the rarest were visits to 6 which were only 30,2%. Overall compliance with ANC visits during the Covid-19 pandemic at Public Health Center as many as 79,4% of pregnant women did not comply with ANC. ANC visit compliance during the Covid-19 pandemic based on its characteristics 61,9% of mothers aged 20-35 years did not comply with ANC, 54% of mothers with more than once parity were not compliant, 31,7% of mothers with higher education were not compliant ANC, and 60,4% of working mothers are not compliant for ANC.